In Utero exposure to genistein enhanced intranasal house dust mite allergen-induced respiratory sensitization in young adult B6C3F1 mice. (24th June 2016) - Guo, Tai L.; Meng, Andrew H.
Highlights: In utero genistein exposure increased IgE production in young adult offspring. In utero genistein exposure increased antigen-specific IgG subclasses. In utero genistein exposure increased lung macrophage number. Abstract: Despite many hypothesized benefits of dietary isoflavone genistein (GEN) deriving from soy-based products, questions surrounding GEN's developmental immunotoxic effects are increasing. To understand how in utero GEN exposure may modulate postnatal respiratory sensitization, we conducted a time course study using a common household allergen (house dust mites: HDM; 10 μg/mouse) following intranasal instillation, a physiological route of allergen exposure. GEN was administered to dams by gavage from gestational day 14 to parturition at a physiologically relevant dose (20 mg/kg bw). Female and male offspring were sensitized with HDM allergens beginning about one month prior to sacrifice followed by challenges with three weekly doses of HDM extracts, and they were euthanized at day 3 following the final HDM exposure at four different time points (postnatal day (PND) 80, 120, 160, and 200). In utero GEN combined with postnatal HDM exposures (GEN + HDM) increased total IgE production in both young female and male B6C3F1 offspring ( e.g., PND 80 in females and PND 120 in males). Increased antigen-specific IgG1, IgG2a and IgG2b levels were also observed at various time points in both female and male offspring. In addition, increases in macrophage number in bronchoalveolar lavage fluid of both female and male GEN + HDM offspring at PND 80 and PND 120, respectively, were observed when compared to the vehicle group. For T cells, an increase over the vehicle in female GEN + HDM offspring was observed at PND 80. Due to similar patterns of increases, it seems likely that GEN + HDM-induced increases in total IgE and macrophages are related. Overall, in utero GEN plus later-life HDM exposures exert increases in total IgE and HDM-specific IgG production as well as macrophage recruitments to the lung in young adult mice.